2014
DOI: 10.14260/jemds/2014/2087
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Low T3 Syndrome in Chronic Heart Failure

Abstract: BACKGROUND: Thyroid abnormalities are common in chronic heart failure. Severity of heart failure rises by several fold in patients with thyroid dysfunction. OBJECTIVES: The purpose of this cross sectional comparative study is to determine the correlation between low T3 syndrome and chronic heart failure & predicting the severity of chronic heart failure. METHODS: In this descriptive, cross sectional study, all patients who presented to the Department of medicine with chronic heart failure during this study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It agrees with the findings of (Green, 2007), that parents are often involved in their children education and other aspects of their lives. Over the years, findings have demonstrated that parent's involvement in the education of the children is beneficial to all parents, children, and schools (Gina & Ronel, 2014). According to Samuel et al (2015) in a magazine report of 2002, six types of programmes could be utilized by schools to build strong parental skills .These are: school can assist families with parenting and childrearing skills; schools can communicate with families about school programmes and students' progress and needs; work to improve families as volunteers in school activities; encourage families to be involved in learning activities at home; include parents as participants in important schools decisions, and coordinate with business and agencies to provide resources and services for families, student, and the community this will to a large extend aid student performance in science subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It agrees with the findings of (Green, 2007), that parents are often involved in their children education and other aspects of their lives. Over the years, findings have demonstrated that parent's involvement in the education of the children is beneficial to all parents, children, and schools (Gina & Ronel, 2014). According to Samuel et al (2015) in a magazine report of 2002, six types of programmes could be utilized by schools to build strong parental skills .These are: school can assist families with parenting and childrearing skills; schools can communicate with families about school programmes and students' progress and needs; work to improve families as volunteers in school activities; encourage families to be involved in learning activities at home; include parents as participants in important schools decisions, and coordinate with business and agencies to provide resources and services for families, student, and the community this will to a large extend aid student performance in science subjects.…”
Section: Discussionmentioning
confidence: 99%